Photoactivated Platinum Complexes: Targeting Membrane Proteins and Organelles for Precision Cancer Therapy - Shu Chen; Qiyuan Zhou; Jiaqian Xu; Guangyu Zhu (Angewandte Chemie International Edition, 2026)
ABSTRACT Photodynamic therapy (PDT) and photoactivated chemotherapy (PACT) have emerged as promising anticancer modalities due to their noninvasive nature, spatiotemporal precision, and high tumor suppression efficacy. Integrating platinum with these phototherapies addresses key limitations of conventional platinum chemotherapy, specifically systemic toxicity and pervasive drug resistance. Since cancer cell membrane proteins, including receptors and transporters, and subcellular organelles play a pivotal role as therapeutic targets, directing platinum phototherapeutics to membrane proteins or specific organelles markedly enhances efficacy compared to nonspecific targeting. Consequently, membrane protein‐ and organelle‐targeted platinum‐based phototherapeutics represent a transformative advance in cancer treatment. This review highlights recent advancements in membrane protein‐/organelle‐targeted and photoactivated platinum complexes and explains how targeting improves efficacy, reduces resistance, and has the potential to minimize off‐target toxicity. We examine the therapeutic benefits derived from localized generation of reactive oxygen species, light‐triggered release of cytotoxic species, and activation of organelle‐specific cell death pathways. These insights may guide the rational design of next‐generation photoactivatable platinum complexes, offering opportunities for improved therapeutic outcomes through synergistic mechanisms and precise targeting strategies.